2007
DOI: 10.1111/j.1751-2980.2007.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in gastrointestinal disease in the Asia–Pacific region

Abstract: The new millennium has seen distinct changes in the pattern of gastrointestinal disease in the Asia–Pacific region. These changes are important as more than half of the world's population come from the region and therefore impact significantly on the global disease burden. The highest incidence of gastric cancer (GCA) has been reported from Asia and GCA remains a very important cancer. However time‐trend studies have shown a decrease in GCA incidence in several countries in Asia. A rise in cardio‐esophageal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 46 publications
2
51
0
2
Order By: Relevance
“…There have been considerable changes in the epidemiology of upper gastrointestinal (GI) disease in the Asia-Pacific region over the past decade (1). A decline in the prevalence of peptic ulcer disease in the West over the past three to four decades has been reported (2).…”
Section: Introductionmentioning
confidence: 99%
“…There have been considerable changes in the epidemiology of upper gastrointestinal (GI) disease in the Asia-Pacific region over the past decade (1). A decline in the prevalence of peptic ulcer disease in the West over the past three to four decades has been reported (2).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, it is the second and third highest ranked cancer in mortality and incidence, respectively (1). The incidence of colorectal cancer is also rising rapidly in other parts of the world including several Asian countries for which westernized dietary lifestyle has been implicated as the major cause (2,3). Five-year survival is dramatically improved if diagnosis is made at early stages, but limited access to effective colonoscopic screening remains a problem (1).…”
Section: Introductionmentioning
confidence: 99%
“…CD is characterized by transmural inflammatory lesions that affect virtually any part of the gastrointestinal tract (Raelson et al, 2007). In the past few decades, CD was thought to be a "western" disease, with higher prevalence rates reported in developed countries, relative to those of Asia (Yang et al, 2001;Goh, 2007). However, recent epidemiological studies have revealed an increasing trend in CD incidence and prevalence rates in this geographical region (Yang et al, 2001;Leong et al, 2004;Ouyang et al, 2005).…”
Section: Introductionmentioning
confidence: 94%